Pengaruh Modifikasi Pembelajaran Menggunakan Media Kardus Terhadap Hasil Belajar Lompat Jauh Gaya Jongkok Pada Siswa Kelas VI SD Negeri Sidomukti III Bojonegoro - Dwi Retno Aryaningtyas; Muhammad Muhyi Faruq; Yandika Fefrian Rosmi (STKIP PGRI SUMENEP, 2022)
This study was to determine the effect of learning modification using cardboard media on learning outcomes squat-style long jump in grade VI SD Negeri Sidomukti III Bojonegoro. This research is an experimental study that focuses on